2009
DOI: 10.1111/j.1365-2583.2009.00896.x
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoglobulin superfamily is conserved but evolved rapidly and is active in the silkworm, Bombyx mori

Abstract: Immunoglobulin superfamily (IgSF) proteins are known for their abilities to specifically recognize and adhere to cells. In this paper, we predicted the presence of 133 IgSF proteins in the silkworm (Bombyx mori) genome. Comparison with similar proteins in other model organisms (Caenorhabditis elegans, Drosophila melanogaster, Anopheles gambiae, Apis mellifera and Homo sapiens) indicated that IgSF proteins are conserved but have rapidly evolved from worms to human beings. However, these proteins are well conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
3
1
Order By: Relevance
“…Lrig1 (A006920), a leucine-rich repeat immunoglobulin involved in the pathogen response, was also upregulated at 24 hpi [86]. However, two dscam genes (dscam2 and dscam5), known to be involved in cell adherence, were shown to be downregulated in this study [87], [88].…”
Section: Resultscontrasting
confidence: 48%
“…Lrig1 (A006920), a leucine-rich repeat immunoglobulin involved in the pathogen response, was also upregulated at 24 hpi [86]. However, two dscam genes (dscam2 and dscam5), known to be involved in cell adherence, were shown to be downregulated in this study [87], [88].…”
Section: Resultscontrasting
confidence: 48%
“…It has been suggested that the induced lysozymes disturb the formation of the spore wall. Immunoglobulin superfamily (IgSF) proteins are known for their ability to specifically recognize and adhere to cells [67]. Four immunoglobulin encoding genes, IG2 (sw02946), IG6 (sw20465), IG8 (sw09094) and IG9 (sw01099), were induced, and three were up-regulated, suggesting a function for binding to the spores and neutralizing harmful effects [68].…”
Section: Resultsmentioning
confidence: 99%
“…About 125 g of artificial food and 50 mL of concentrated bacterial solution (OD 600 ≈ 100) were thoroughly mixed in a beaker, cut into fine grains and fed to the silkworms. The midgut, integument and hemolymph from five individuals were anatomized at 24 h after infection (Huang et al ., 2009b; Huang et al ., 2009a) and stored at –80°C until required.…”
Section: Methodsmentioning
confidence: 99%